Analysis of Double Pulsing Effect in Motor Drives Based on Vector Diagram - Kang, Byeong Woo; Lee, Kyo Beum (Conference Proceedings - IEEE Applied Power Electronics Conference and Exposition - APEC, 2025)
This paper analyzes the double pulsing effect based on vector diagram in motor drives with variable modulation techniques. The overvoltage caused by voltage reflection is analyzed in a long transmission line between an inverter and a motor. The region where the double pulsing effect occurs is compared and analyzed through voltage vector diagrams of different modulation techniques. A modulation index and an on-time of a zero-voltage vector are considered to generalize the region where the double pulsing effect occurs. The validity of the analysis on the region where the double pulsing effect occurs with variable modulation techniques is verified through simulation results.
Keywords: Long transmission lines; Modulation indexes; Modulation techniques; Motor drive; Over-voltages; Paper analysis; The double pulsing effect; Vector-diagrams; Voltage vectors; long transmission line; modulation techniques; The double pulsing effect; vector diagram